Laboratory evaluation on temporary plugging performance of degradable preformed particle gels (DPPGs). (1st April 2021) - Zhu, Daoyi; Xu, Zenghao; Sun, Renxian; Fang, Xingyu; Gao, Dawei; Jia, Xiaobo; Hu, Jingru; Weng, Jintao
Highlights: Degradable preformed particle gels (DPPGs) were employed as temporary plugging agent (TPA). DPPGs showed excellent plugging strength and self-degradability. Effects of different factors on the temporary plugging performance of DPPGs were studied. Temporary blocking mechanism of DPPGs was explained. Abstract: In recent years, granular temporary plugging agents (TPA) have been widely studied, especially in repeated fracturing operations, to stimulate oil and gas production in unconventional petroleum reservoirs. They can divert the hydraulic fracturing energy to form more complex fractures that make oil and gas more easily flow into production well. Pre-formed particle gels (PPGs), as deformable particles, are often used in petroleum reservoir water management operations because of their high strength, simple fabrication process, and environmental friendliness. However, their application as TPA is rarely reported. In this paper, degradable PPGs (DPPGs) were employed, and their temporary plugging performance was studied in the laboratory. Bottle tests were first conducted to investigate the swelling and degradation performance. Results show that DPPGs exhibit good swelling ability in an extended range of brine salinity (20000 to 400000 ppm), and DPPGs can be fully degraded, and the degradation time increase with temperature. According to the temporary plugging performance by core flooding experiments, the plugging strength increased with the injection pressure, dry particle size, and swelling ratio (less than 20 times). However, the addition of smaller size particles will prevent large particles from forming deformable blockage on the matrix end surface, and subsequent water flow channels will be easily created, so the plugging performance of the DPPGs will decrease. The above experimental results can provide an experimental and theoretical basis for the application of DPPGs in repeated fracturing operations in unconventional reservoirs.